The Intricate Relationship between Psychotic-Like Experiences and Associated Subclinical Symptoms in Healthy Individuals - Unterrassner, Lui; Wyss, Thomas A.; Wotruba, Diana; Haker, Helene; Rössler, Wulf (Frontiers in Psychology, 2017)
The interplay between subclinical psychotic, negative, and affective symptoms has gained increased attention regarding the etiology of psychosis spectrum and other mental disorders. Importantly, research has tended to not differentiate between different subtypes of psychotic-like experiences (PLE) although they may not have the same significance for mental health. In order to gain information on the subclinical interplay between specific PLE and other symptoms as well as the significance of PLE for mental health, we investigated their specific associations in 206 healthy individuals (20–60 years, 73 females) using correlational and linear regression analyses. PLE were assessed with the Magical Ideation Questionnaire, the revised Exceptional Experiences Questionnaire, and subscales of the Schizotypal Personality Questionnaire (SPQ). The revised Symptom Checklist 90, the SPQ, and the Physical Anhedonia Scale were used to measure subclinical negative symptoms, affective symptoms, and other symptoms such as, emotional instability. As hypothesized, we found that (1) most affective symptoms and all other subclinical symptoms correlated positively with all PLE, whereas we found only partial associations between negative symptoms and PLE. Notably, (2) magical ideation and paranormal beliefs correlated negatively with physical anhedonia. In the regression analyses we found (3) similar patterns of specific positive associations between PLE and other subclinical symptoms: Suspiciousness was a specific predictor of negative-like symptoms, whereas ideas of reference, unusual perceptual experiences, and dissociative anomalous perceptions specifically predicted anxiety symptoms. Interestingly, (4) ideas of reference negatively predicted physical anhedonia. Similarly, paranormal beliefs were negatively associated with constricted affect. Moreover, odd beliefs were a negative predictor of depression, emotional instability, and unspecific symptoms. Our findings indicated that subtypes of PLE are differentially implicated in psychological functioning and should therefore not be categorized homogeneously. Moreover, paranormal beliefs, odd beliefs, and partly ideas of reference might also contribute to subjective well being in healthy individuals. Our results might serve as a starting point for longitudinal studies investigating the interplay of subtypes of subclinical symptoms along a psychopathological trajectory leading to mental disorders. Importantly, this research might help to improve therapeutic strategies for psychosis prevention.